Recommendations for diagnosis and treatment of methemoglobinemia. Issue 12 (23rd September 2021) - Iolascon, Achille; Bianchi, Paola; Andolfo, Immacolata; Russo, Roberta; Barcellini, Wilma; Fermo, Elisa; Toldi, Gergely; Ghirardello, Stefano; Rees, Davis; Van Wijk, Richard; Kattamis, Antonis; Gallagher, Patrick G.; et al.
Abstract: Methemoglobinemia is a rare disorder associated with oxidization of divalent ferro‐iron of hemoglobin (Hb) to ferri‐iron of methemoglobin (MetHb). Methemoglobinemia can result from either inherited or acquired processes. Acquired forms are the most common, mainly due to the exposure to substances that cause oxidation of the Hb both directly or indirectly. Inherited forms are due either to autosomal recessive variants in the CYB5R3 gene or to autosomal dominant variants in the globin genes, collectively known as HbM disease. Our recommendations are based on a systematic literature search. A series of questions regarding the key signs and symptoms, the methods for diagnosis, the clinical management in neonatal/childhood/adulthood period, and the therapeutic approach of methemoglobinemia were formulated and the relative recommendations were produced. An agreement was obtained using a Delphi‐like approach and the experts panel reached a final consensus >75% of agreement for all the questions.